2016
DOI: 10.3390/ijms17091451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Novel Compound LX519290, a Derivative of l-allo Threonine, on Antioxidant Potential in Vitro and in Vivo

Abstract: We investigated the antioxidative activity of LX519290, a derivative of l-allo threonine, in vitro and in vivo. To evaluate the antioxidative activity of LX519290, we performed several in vitro assays (2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis-(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) radical-scavenging assays, a ferric reducing antioxidant power assay, cupric-reducing antioxidant capacity, and oxygen radical absorbance capacity assay) and evaluated inhibition against the generation of nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Macrophages are usually employed to evaluate the response to oxidative stress for host defense. Hydrogen peroxide (H 2 O 2 ) is commonly used for inducing oxidative stress-mediated cell injury in various kinds of cells [44,45]. We confirmed that 600 µM H 2 O 2 was sufficient to induce oxidative injury in RAW 264.7 macrophages.…”
Section: Discussionsupporting
confidence: 65%
“…Macrophages are usually employed to evaluate the response to oxidative stress for host defense. Hydrogen peroxide (H 2 O 2 ) is commonly used for inducing oxidative stress-mediated cell injury in various kinds of cells [44,45]. We confirmed that 600 µM H 2 O 2 was sufficient to induce oxidative injury in RAW 264.7 macrophages.…”
Section: Discussionsupporting
confidence: 65%
“…It is well known that SOD1 is rapidly converted the O 2 − into H 2 O 2 which is subsequently detoxified to H 2 O by GPx and CAT [ 15 , 22 ]. Continuous exposure of oxidative stress may cause the damage of these primary antioxidant enzyme, which play a crucial role in cellular homeostasis during cell proliferation, and can develop various degenerative diseases [ 23 ]. In this study, NNFE treatment significantly increased both the mRNA and protein level of the antioxidant enzymes SOD1, CAT, and GPx-1 in RAW 264.7 cells and BV2 cells ( Figure 4 A,B, and Supplementary data Figure S10 , respectively), indicating that NNFE has the ability to maintain cellular homeostasis and to protect the cell from oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…MS15 treatment has been competent to enhance the translational and transcriptional levels of HO-1 and, in line with previous therapies, facilitates the Nrf-2 translocation in a concentration-reliant way into the nucleus. The process suggests that the antioxidant properties of MS15 are partly due to the concentration-dependent initiation of HO-1 in RAW 264.7 cells, controlled by dose-reliant activation of Nrf-2 [ 49 ]. However, the inhibition of the HO-1 role by HO-1 inhibitor considerably hindered those protective impacts of MS15 against H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%